Ru Monoimines with Extended Excited-State Lifetimes and Geometrical Modulation of Photoinduced Mixed-Valence Interactions - Ramirez-Wierzbicki, Ivana; Pieslinger, German E.; Aramburu-Troselj, Bruno M.; Abate, Pedro O.; Cadranel, Alejandro (Inorganic Chemistry, 2023)
The photophysical properties of monodentate-imine ruthenium complexes do not usually fulfil the requirements for supramolecular solar energy conversion schemes. Their short excited-state lifetimes, like the 5.2 ps metal-to-ligand charge transfer (MLCT) lifetime of [Ru(py)4Cl(L)]+ with L = pz (pyrazine), preclude bimolecular or long-range photoinduced energy or electron transfer reactions. Here, we explore two strategies to extend the excited-state lifetime, based on the chemical modification of the distal N atom of pyrazine. On one hand, we used L = pzH+, where protonation stabilized MLCT states, rendering thermal population of MC states less favorable. On the other hand, we prepared a symmetric bimetallic arrangement in which L = (μ-pz)Ru(py)4Cl to enable hole delocalization via photoinduced mixed-valence interactions. A lifetime extension of 2 orders of magnitude is accomplished, with charge transfer excited states living 580 ps and 1.6 ns, respectively, reaching compatibility with bimolecular or long-range photoinduced reactivity. These results are similar to those obtained with Ru pentaammine analogues, suggesting that the strategy employed is of general applicability. In this context, the photoinduced mixed-valence properties of the charge transfer excited states are analyzed and compared with those of different analogues of the Creutz-Taube ion, demonstrating a geometrical modulation of the photoinduced mixed-valence properties.
CRIS-Team Scopus Importer:2023-03-24